2018
DOI: 10.1002/ncp.10224
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravenous Lipid Emulsions Containing Fish Oil on Clinical Outcomes in Critically Ill Surgical Patients: A Literature Review

Abstract: A fish oil (FO)–containing intravenous lipid emulsion (ILE; FO ILE) has been approved for use in the United States; however, similar formulations have been used throughout Europe and China in intensive care units since the 1990s. This literature review evaluates the evidence regarding the effectiveness of FO ILE on clinical outcomes in the critically ill surgical patient population. The review of available evidence demonstrates that ILEs containing FO lower triglyceride concentrations, inflammatory markers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
12
0
3
Order By: Relevance
“…Fish oil contains ω-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]) that incorporate into cell membranes influencing various transcription factors modifying the expression of genes involved in many biological processes which include metabolism, immune function, and inflammation [3]. ILEs based on fish oil have been shown to have anti-inflammatory and immunomodulatory effects [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fish oil contains ω-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]) that incorporate into cell membranes influencing various transcription factors modifying the expression of genes involved in many biological processes which include metabolism, immune function, and inflammation [3]. ILEs based on fish oil have been shown to have anti-inflammatory and immunomodulatory effects [5].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PN it is not uncommon to experience increases in serum triglyceride concentrations and hypertriglyceridemia correlated with hepatic steatosis, which can contribute to liver damage. In this regard, ILEs based on fish oil may be protective against rapid increases in serum triglycerides, compared with other formulas such as those based on MCT/LCT, although the evidence is not conclusive [5,20]. In our study we did not observe any differences in the percentage of patients that developed hypertriglyceridemia (levels above 400 mg/dL) which was, in any case, low in both groups (5% in the n-3 PUFA group and 7.4% in the other group); nonetheless, we observed significant reductions of levels of serum triglycerides in the n-3 PUFA group.…”
Section: Lipid Control and Liver Enzymesmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, the positive modulation of the inflammatory process also involves the incorporation of EPA and DHA into cell membranes, which causes a decrease in the concentration of arachidonic acid in phospholipid membranes and, as a consequence, the reduction in the production of pro-inflammatory eicosanoids [69,70]. The authors of the latest review concerning the impact of intravenous lipid emulsions containing fish oil on clinical outcomes in critically ill surgical patients demonstrated that those lipid emulsions positively affect the functioning of the body by lowering triglyceride concentrations, inflammatory markers, and liver function enzymes, improving patients morbidity and mortality [71].…”
Section: Immunomodulatory Nutritionmentioning
confidence: 99%